2007
DOI: 10.1017/s1355617707071512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of memory impairment on training outcomes in ACTIVE

Abstract: Cognitive training improves mental abilities in older adults, but the trainability of persons with memory impairment is unclear. We conducted a subgroup analysis of subjects in the Advanced Cognitive Training for Independent and Vital Elderly (ACTIVE) trial to examine this issue. ACTIVE enrolled 2802 non-demented, community-dwelling adults aged 65 years and older and randomly assigned them to one of four groups: Memory training, reasoning training, speed-of-processing training, or no-contact control. For this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(86 citation statements)
references
References 27 publications
5
77
0
4
Order By: Relevance
“…The small sample size may have resulted in the failure to detect a group effect or a group by time effect. These results thus appear partly compatible with previous studies in which cognitive training programmes in the MCI-A population applying specific memory techniques (e.g., cueing, EL learning, EF learning, SR, method of loci), alone or in combination, appear to offer some efficacy, either on direct measures of training or on objective and/or subjective measures of cognition (Akhtar et al, 2006;Belleville et al, 2006;Clare et al, 2009;Greenaway et al, 2008;Hampstead et al, 2008;Jean et al, 2007;Kinsella et al, 2009;Kurz et al, 2009;Londos et al, 2008;Rapp et al, 2002;Rozzini et al, 2007;Talassi et al, 2007;Troyer et al, 2008;Unverzagt et al, 2007;Wenisch et al, 2007). The fact that some secondary outcomes were not re-administered at the end of the intervention, but only at 5-week follow-up, weakens the conclusions about the effect of interventions on these outcomes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The small sample size may have resulted in the failure to detect a group effect or a group by time effect. These results thus appear partly compatible with previous studies in which cognitive training programmes in the MCI-A population applying specific memory techniques (e.g., cueing, EL learning, EF learning, SR, method of loci), alone or in combination, appear to offer some efficacy, either on direct measures of training or on objective and/or subjective measures of cognition (Akhtar et al, 2006;Belleville et al, 2006;Clare et al, 2009;Greenaway et al, 2008;Hampstead et al, 2008;Jean et al, 2007;Kinsella et al, 2009;Kurz et al, 2009;Londos et al, 2008;Rapp et al, 2002;Rozzini et al, 2007;Talassi et al, 2007;Troyer et al, 2008;Unverzagt et al, 2007;Wenisch et al, 2007). The fact that some secondary outcomes were not re-administered at the end of the intervention, but only at 5-week follow-up, weakens the conclusions about the effect of interventions on these outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…A recent review of the literature performed by our group (Jean, Bergeron, Thivierge, & Simard, in press) found that prior to July 2009, 15 studies using Petersen's MCI-A criteria have investigated cognitive training and/or stimulation in MCI-A (Akhtar, Moulin, & Bowie, 2006;Belleville et al, 2006;Clare et al, 2009;Greenaway, Hanna, Lepore, & Smith, 2008;Hampstead, Sathian, Moore, Nalisnick, & Stringer, 2008;Jean, Simard, van Reekum, & Bergeron, 2007;Kinsella et al, 2009;Kurz, Pohl, Ramsenthaler & Sorg, 2009;Londos et al, 2008;Rapp, Brenes, & Marsh, 2002;Rozzini et al, 2007;Talassi et al, 2007;Troyer, Murphy, Anderson, Moscovitch, & Craik, 2008;Unverzagt et al, 2007;Wenisch et al, 2007). Cognitive training aims at offering a guided practice on a particular task whereas cognitive stimulation aims at increasing cognitive and social functioning using a non-specific approach (Clare & Woods, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Belleville, Bherer, Lepage, Chertkow, and Gauthier (2008) have reported improved spatial switching capacities following brief practice. Furthermore, Unverzagt et al (2007) showed that "memory-impaired" older adults benefited as much as did healthy older adults from 10 training sessions of 60 -75 minutes (over five to six weeks; in small groups) using the computerised divided attention search task described previously in the ACTIVE study. These effects were maintained up to two years, following four 75-minute booster sessions over three weeks.…”
Section: Introductionmentioning
confidence: 86%
“…Given the relative lack of tests and growing importance of such measures, it is clear that the development of ecologically valid tests would benefit rehabilitation research as well as the general field of Neuropsychology. 5,7,15,16,17,18,24,25,27,30,31,33 12 Narrative memory (other) 3,23,28,30 18,23,26,33, 15,21,22,30,31,33 6 Rivermead Behavioural Memory Test (RBMT) 7,8,16,17,26,27,31,33,34 3,7,23,30,31,36 1,3,4,5,15,28,29,32 1 The ...…”
Section: Methodological Challenge 4: Outcome Measuresmentioning
confidence: 99%